La calidad de los servicios y la satisfacción de los usuarios del gobierno autónomo descentralizado municipal del cantón Penipe. - Medina Casco, Tania Elizabeth (2025)
The research objective was to identify the impact of the quality of the services of the municipal decentralized autonomous government of the Penipe canton and its effect on user satisfaction. For this purpose, the hypothetical-deductive method and field research are considered, which identify the impact of the quality of the services. The population under study corresponds to, on the one hand, 7,155 inhabitants, with a PEA reference of 2,979 and a representative sample of 245 people. Furthermore, a population of 150 officials of the municipal decentralized autonomous government of the Penipe canton with its respective sample of 30 officials, through the application of surveys, the objective set in the research will be achieved. A hypothesis was proposed in the research, and the SPSS statistical software, using the Chi-square method, was used to verify it. The results indicate that the quality of the services of the Municipal Decentralized Autonomous Government of the Canton Penipe affects user satisfaction. The study raises the need to consider officials' involvement within the environment where services are developed to provide the service in the best way. Likewise, customer satisfaction is based on the importance that authorities give to meeting users' needs, generating growth, and developing and sustaining the Penipe canton.